Unexpected crystallographic structure, phase transformation, and hardening behavior in the AlCoCrFeNiTi0.2 high-entropy alloy after high-dose nitrogen ion implantation. (April 2022) - Jenczyk, Piotr; Jarzabek, Dariusz M.; Lu, Zhang; Gadalińska, Elżbieta; Levintant-Zayonts, Neonila; Zhang, Yong
Graphical abstract: Highlights: Very high dose of nitrogen ions implanted into AlCoCrFeNiTi0.2 high entropy alloy. Unidentified XRD spectrum which we tentatively attribute to the creation of new high or medium entropy ceramics. Promising and interesting properties – higher hardness and wear resistance on one hand and higher hardness-to-Young's modulus ratio on the other hand. Abstract: Harsh environments, such as nuclear power plants, require the development of materials with stable properties when exposed to radiation/bombardment conditions. In this work, a bulk high-entropy alloy (HEA) was implanted with nitrogen ions accelerated at 50 kV to induce and study crystal structural defects. X-ray powder diffraction (XRD) showed that the studies HEA consisted of two phases—σ and body-centered cubic (BCC)—and underwent the σ to BCC phase transformation due to ion bombardment. Unexpectedly, XRD peaks of implanted samples could not be assigned to any known simple nitride, a finding that suggests the creation of new high- or medium-entropy ceramics. Studies of the mechanical and tribological properties with the use of nanoindentation and scratch tests revealed a hardening of both phases of the implanted surface and higher wear resistance. There were also surprising increases in the hardness-to-Young's modulus ratio and elastic recovery for both phases. The results are promising not only for the nuclear applications, but also for space applications, mechanical engineering, and tribology.